Production of bioethanol from waste paper by yeast fermentation - Nor Hanis Akila, Razali (2025)
In a recent study, waste paper was utilized as a feedstock for the production of bioethanol, categorizing it as lignocellulosic biomass. The waste paper underwent a pretreatment process involving acid hydrolysis with a 5% sulfuric acid solution to release fermentable sugars. This acid hydrolysis was systematically conducted using varying volumes of acid involving 10 mL, 15 mL, 20 mL, and 25 mL per gram of waste paper to determine the optimal yield of hydrolysate. The results indicated that an acid volume of 15 mL/g achieved the highest hydrolysate yield and was subsequently employed for acid hydrolysis of samples containing 5 g, 10 g, and 15 g of waste paper. Following the hydrolysis process, the resulting hydrolysate was subjected to fermentation after adjusting the pH to a range of 4.0 to 4.5 using sodium hydroxide (NaOH). The fermentation utilized the yeast Saccharomyces cerevisiae, which effectively converted the released sugars into bioethanol, the primary product of interest. Notably, the highest bioethanol yield recorded was 34.60% for the 10 g loading, while yields for the 5 g and 15 g loadings were measured at 33.17% and 22.75%, respectively. This study highlights the potential of waste paper as a viable resource for sustainable bioethanol production and the importance of optimizing pretreatment and fermentation conditions to enhance overall yields.